The 5E Learning Cycle: A Pathway to Better Science Problem-Solving Skills through Classcraft Gamification - Sabar Nurohman; Makmum Makmudah; Rizki Arumning Tyas (Postgraduate, University of Mataram, 2024)
Problem-solving skills are essential for students to navigate both academic challenges and real-world situations effectively. However, many junior high school students struggle to develop these skills, particularly in science education. This study aims to explore the effects of gamification, using Classcraft, integrated into the 5E Learning Cycle model on the science problem-solving skills of seventh-grade students. Conducted as a quasi-experimental study with a non-equivalent control group pretest-posttest design, the research involved a cluster random sample of public junior high schools in Yogyakarta. A pretest-posttest problem-solving skills test was administered, with instruments validated using Pearson correlation and reliability measured through Cronbach's alpha. Data analysis employed independent sample t-tests and effect size to determine the impact of the intervention. The results demonstrate that Classcraft-assisted gamification within the 5E Learning Cycle significantly enhances students' problem-solving abilities. This suggests that integrating gamification into instructional models not only boosts engagement but also fosters critical thinking skills crucial for everyday decision-making and problem resolution, thereby equipping students with practical skills applicable to real-life situations.